1994
DOI: 10.1183/09031936.94.07020392
|View full text |Cite
|
Sign up to set email alerts
|

From allergen sources to reduction of allergen exposure

Abstract: F Fr ro om m a al ll le er rg ge en n s so ou ur rc ce es s t to o r re ed du uc ct ti io on n o of f a al ll le er rg ge en n e ex xp po os su ur re e J.C. Bessot, F. de Blay, G. PauliFrom allergen sources to reduction of allergen exposure. J.C. Bessot, F. de Blay, G. Pauli. ERJ Journals Ltd. 1994. ABSTRACT: Allergen exposure plays a major role in the development of sensitization, inflammation and symptomatic asthma. The development of new means of detecting allergens has enabled the evaluation of the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The major cat allergen, Fel d 1, is mainly found in the sebaceous glands of the skin, but also in the salivary glands [ 9]. Fel d 1 has an apparent molecular weight (MW) of about 35 kDa by HPLC gel filtration and 18 kDa in SDS‐PAGE, confirming that it is a non‐covalently linked dimer [ 10].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The major cat allergen, Fel d 1, is mainly found in the sebaceous glands of the skin, but also in the salivary glands [ 9]. Fel d 1 has an apparent molecular weight (MW) of about 35 kDa by HPLC gel filtration and 18 kDa in SDS‐PAGE, confirming that it is a non‐covalently linked dimer [ 10].…”
Section: Introductionsupporting
confidence: 75%
“…Dog allergens are mainly found in skin, but also in serum and saliva [ 9, 15]. The major allergen Can f 1, has been found to have a MW of 22 kDa in HPLC‐gel filtration and 25 kDa in SDS‐PAGE with an additional band at 18 kDa [ 16].…”
Section: Introductionmentioning
confidence: 90%
“…Although very few pollen grains can reach the lower airways, these allergens may be born on submicronic particules [58] and are present in intracellular starch granules within pollen grains [59]. Pollen grains are ruptured in rainwater by osmotic shock, each grain releasing about 700 starch granules into the environment.…”
Section: Consequences Of the Activation Of Igementioning
confidence: 99%
“…Several allergen avoidance programmes have been introduced in recent decades [12][13][14]. Besides the removal of allergen sources (domestic animals, old mattresses, old carpets) it has been shown that the introduction of smooth floor coverings (nontextile), low levels of indoor air humidity, increased air ventilation, and the application of allergen-impermeable mattress and pillow covers, are measures which can contribute to diminished exposure to HDM allergens, and which may be accompanied by improvement of clinical symptoms [15][16][17].…”
mentioning
confidence: 99%